Cesarean scar pregnancy and Successful treatment: Case series - Jelveh Jalili; Malihe Afiat; Fatemeh Tara; Naghme Khorsand; Ali Javidi (Mashhad University of Medical Sciences, 2017)
Introduction: One of the types of EP is Cesarean Scar Pregnancy (CSP) that its diagnosis is difficult and can cause serious complications such as uterine rupture, profuse hemorrhage and even maternal death. This study was performed with aim to report some rare cases of CSP and the successful treatment. Case presentation: The first case was a woman with history of 2 previous C/S with gestational age of 8 weeks. In TVS which was performed by radiologist, she had a gestational sac with a fetal pole having heart rate in cesarean scar. The patient underwent laparotomy and wedge resection of CSP. The second and third patients were detected with spotting and menstrual retard, and transvaginal sonography detected gestational sac with 6.5 & 7 weeks in the cesarean scar and were treated with elective intragestational sac methotrexate injections by ultrasound guidance and then curettage. Conclusion: CSP is a rare condition with serious complications. For early diagnosis, one must consider high clinical suspicion for detecting it in patients with previous C/S, and appropriate interventional treatment leads to decreased maternal morbidity and mortality.